2015
DOI: 10.1038/ncomms8153
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic control of contractile function in skeletal muscle

Abstract: Optogenetic stimulation allows activation of cells with high spatial and temporal precision. Here we show direct optogenetic stimulation of skeletal muscle from transgenic mice expressing the light-sensitive channel Channelrhodopsin-2 (ChR2). Largest tetanic contractions are observed with 5-ms light pulses at 30 Hz, resulting in 84% of the maximal force induced by electrical stimulation. We demonstrate the utility of this approach by selectively stimulating with a light guide individual intralaryngeal muscles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 30 publications
(36 reference statements)
7
86
0
Order By: Relevance
“…The light intensity before and after passing through the device is shown in Figure S16 in the Supporting Information, which is high enough to stimulate deep muscles. [ 60 ] Optical stimulationinduced muscle activation and EMG signals are recorded simultaneously (40 Hz, 464 mW m −2 fi xed; Figure 6 …”
Section: Optical Stimulation and Electrophysiological Recording In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…The light intensity before and after passing through the device is shown in Figure S16 in the Supporting Information, which is high enough to stimulate deep muscles. [ 60 ] Optical stimulationinduced muscle activation and EMG signals are recorded simultaneously (40 Hz, 464 mW m −2 fi xed; Figure 6 …”
Section: Optical Stimulation and Electrophysiological Recording In Vivomentioning
confidence: 99%
“…Optimized conditions of the light impulses for maximum excitation of peripheral motor neurons are experimentally determined through recording EMG signals under different light frequencies and intensities. [ 21,60 ] Figure 6 e shows the processed EMG signals to present their amplitudes [ 61 ] under different frequencies (464 mW m −2 is fi xed) of light impulses applied to hind limb muscles (fi ltered EMG shown in Figure S17 in the Supporting Information). We found that 40 Hz optical stimulation shows the highest amplitude of EMG.…”
Section: D)mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a recent development in terms of using optogenetics to control muscle function is the use of direct optogenetic control of muscle contraction, using both transgenic ChR2 expressing mice and viral transduction of muscle in vivo, to optically control the muscles of the larynx [46]. This approach may provide a complementary therapy to prevent muscle wasting in the intervening period between muscle denervation and reinnervation by regenerating axons [47].…”
Section: Further Advances Towards Optogenetic Control Of Motor Functionmentioning
confidence: 99%
“…A more commonly used approach in line with gene therapy approaches used in other systems and disease models [24] is the utilization of adeno-associated virus (AAV) vectors to enable optical modulation of muscle activity. These include expression of ChR2 in rat peripheral motor nerves following muscle injection of an AAV vector [18,25] or expression directly in mouse skeletal muscle tissue following systemic injection [26]. While direct optical modulation of muscle tissue is feasible, it would require individual light sources for each targeted muscle, and implanting optical stimulation hardware could be difficult in smaller or deep muscles such as intrinsic hand muscles.…”
Section: Introductionmentioning
confidence: 99%